INNOVATIONS ON THE ADULTS AND SENIORS EDUCATION - Lipphardt, Anne-Marie (Inaugural Age Friendly Universities Conference 2015, 2015)
People age and the number of people aged 55 and above is growing steadily. At the same time old people do not want to be left behind but keep pace with the younger generation. The ever-increasing size of the digital world closely connected with the desire of seniors to engage in learning activities leads to infinite opportunities for further education. To meet the specific requirements of senior learners, innovative learning concepts are needed. The Innovation in Learning Institute (ILI) focuses on innovation processes in learning, training, and skills development. Developing innovative offers for older people is one of the main fields of work. ILI believes that e-learning is a very suitable instrument to deal with the heterogeneity of adult learners and to meet the learners’ needs and pace. In several projects, senior citizens are offered new education opportunities and are thus supported in becoming competent, independent ICT-users. The paper presentation will grant an insight into three successful projects of ILI conducted with and for seniors in the field of technology enhanced learning: · SenApp is a European project developing a training app for seniors · The project Lernkanal supports seniors in making video-clips on how to use new media, e.g. tablets · Within EHLSSA a digital learning infrastructure is developed and three e-learning courses are offered <
Keywords: e-learning; older learners; learning in later life